Effects of absorption pressure and temperature on NH3-H2O-LiBr-TiO2 nanofluid absorption performance and system COP. (25th January 2023) - Jin, Zhenghao; Li, Shuhong; Zhou, Runfa; Xu, Mengkai; Jiang, Weixue; Du, Kai
Highlights: The system COP increase as absorption temperature decreases. The system COP increase as absorption pressure increases. The effect of nanofluid slightly increases as absorption temperature increases. The effect of nanofluid decreases as absorption pressure bigger than 0.31 MPa. The largest improvement in absorption efficiency and COP are 85% and 13.7%. Abstract: Adding nanoparticles can enhance the mass and heat transfer of basic fluid, improving the coefficient of performance(COP) of the absorption refrigeration system(ARS). However, there are few experimental studies on the effects of absorption pressure and temperature on the absorption performance of nanofluid in an actual ARS. Therefore, the TiO2 nanoparticles are added to the NH3 - H2 O – LiBr working fluid. The difference in ammonia mass fraction between the inlet and outlet solution of the absorber (Δ ε 'a ) is compared with when the solution is absorbed saturated (Δ ε a ). The results indicate that the Δ ε 'a and system COP increase when the absorption temperature decreases, the absorption pressure increases, or the TiO2 mass fraction increases. The ratio Δ ε 'a /Δ ε a is used to evaluate the absorption efficiency of the nanofluid. The positive effects of nanofluid on the absorption efficiency and COP slightly increase when absorption temperature increases, but decrease when the absorption pressure is greater than 0.31 MPa. For all of our test groups, the greatest improvement in absorption efficiency is 85 %, and the largest improvement in COP is 13.7 %.